PENYULUHAN HUKUM KESELAMATAN LALU LINTAS: Strategi Mewujudkan Budaya Patuh Hukum Lalu Lintas - Raja Desril; Elviandri Elviandri; Aksar Aksar; Raihana Raihana; Desi Sommaliagustina; Tri Wahyuni Lestari (LPPM UMRI, 2018)
Data on accidents and traffic violations collected by the Riau Regional Police Directorate and from our daily observations illustrates that the level of traffic safety and the level of community compliance with traffic laws / legislation is very alarming, if no strategic steps are taken. in order to increase the level of safety and increase the legal compliance of the community it will cause harm not only to the loss of life and property and psychological but also will cause losses in the economic field. The strategy or effort to increase legal awareness of the community as road users is basically part of orderly traffic. Strategies in increasing community legal awareness include: First, socialization or campaigns to comply with traffic regulations through the installation of banners and socialization. Second, Building the character of discipline. This character building can be started through the teacher's example. Therefore awareness of the instructional teachers is undoubtedly necessary. Security, order, safety and smooth traffic are shared responsibilities. Through this counseling, the character of discipline can be transmitted to all students of Muhammadiyah 3 Vocational School Pekanbaru.